Effect of Polypyrrole on the Electrical, Dielectric and Mechanical Properties of Waterborne Epoxy Coatings - Thai, Thu Thuy; Nguyen, Thuy Duong; Nguyen, Thi Thu Trang; Pham, Gia Vu; Tran, Dai Lam; Nguyen, Anh Son (Communications in Physics, 2020)
In this context, conducting composite based on waterborne epoxy system and polypyrrole (PPy) was investigated. The polypyrrole was synthesized by chemical oxidation polymerization. Its morphology and chemical structure were confirmed by using field emission scanning electron microscopy (FESEM) and Fourier transform infrared spectroscopy (FTIR). Then, PPy was well-dispersed in the epoxy coating and had a good compatibility with the matrix. The effects of PPy on dielectric, electrical and mechanical properties of epoxy/PPy composites was examined. The dielectric constant and electrical conductivity of the coatings increased with addition of PPy fillers. Over to 15 wt. % of PPy loading, the volume resistivity of samples slightly decreased from 6.7 × 1010 to 1.5 × 1010 Ω cm. In contrast, the presence of PPy diminished both impact and abrasion resistance of the epoxy/PPy composites, down to 160 kg cm and 10.2 L/mil, respectively, but they stayed acceptable for the coatings. The results reveal that the epoxy containing polypyrrole is suitable for various electrical and dielectric applications.